Nanoink bridge-induced capillary pen printing for chemical sensors. (13th June 2018) - Kahng, Seong-Joong; Cerwyn, Chiew; Dincau, Brian M; Kim, Jong-Hoon; Novosselov, Igor V; Anantram, M P; Chung, Jae-Hyun
Abstract: Single-walled carbon nanotubes (SWCNTs) are used as a key component for chemical sensors. For miniature scale design, a continuous printing method is preferred for electrical conductance without damaging the substrate. In this paper, a non-contact capillary pen printing method is presented by the formation of a nanoink bridge between the nib of a capillary pen and a polyethylene terephthalate film. A critical parameter for stable printing is the advancing contact angle at the bridge meniscus, which is a function of substrate temperature and printing speed. The printed pattern including dots, lines, and films of SWCNTs are characterized by morphology, optical transparency, and electrical properties. Gas and pH sensors fabricated using the non-contact printing method are demonstrated as applications.